The antiphospholipid antibody syndrome research in patients with retinal venous occlusion - Ilhan, F; Celiker, U; Godekmerdan, A; Kan, E (Elsevier Science Inc, 2005)
Background. The antiphospholipid antibody syndrome (APAS) is a condition associated with abnormal thrombosis and the presence of anticardiolipin antibodies (aCL). Methods. Thirty-two patients (20 male and 12 female) aged between 29 and 75 years (mean +/- SD: 56.4 +/- 12.34) with retinal venous occlusive disease were studied. All patients with a history of venous occlusive disease within the previous 8 months were included in the study. Diagnoses were made by fundus examination and fundus fluorescein angiography (FFA). Anticardiolipin IgM and IgG antibodies, antinuclear antibodies (ANA), and IL-1 beta were investigated in all patients. Results. Neither aCL-IgM nor aCL-IgG was observed as positive in this group. Only four patients were found to be ANA positive. However, serum levels of IL-1 beta were higher than those of controls (p <0.001). Mean IL-1 beta was found to be 18.06 +/- 3.39 pg/mL (mean SE), respectively. IL-1 beta levels were found to be significantly different from those of controls (2.7 +/- 0.68 pg/mL) (p <0.001). In this study, antiphospholipid antibody positivity was not determined in any patients. Conclusions. As a result, IL-1 beta level appears higher in retinal venous occlusive disease. This cytokine measurement might be used as a diagnostic indicator for venous occlusive disease. (C) 2005 IMSS. Published by Elsevier Inc.
Keywords: antiphospholipid antibody syndrome; anticardiolipin antibodies (aCL); IL-1 beta